Pengaruh Ekspor dan Belanja Pemerintah Terhadap Pertumbuhan Ekonomi - Hilwa Shabira; Khairul Amri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This research aims to analyze the influence of exports and government spending on economic growth in Indonesia. Using Time-Series data for the period 1999-2019 and analysis of multiple linear regression models and autoregressive distribution lag (ARDL). The results of this study show that there is a cointegration relationship between economic growth and exports and government spending. The results of multiple linear regression show that exports have an insignificant positive relationship with economic growth, while government spending has an insignificant negative relationship with Indonesia's economic growth. The results using Autoregressive Distributed Lag (ARDL) show that in the long term exports have an insignificant positive effect on economic growth, while in the short term exports have a positive and significant effect on economic growth. Government spending, both in the long and short term, has an insignificant negative effect on economic growth. This finding has the implication that increasing economic growth can be done by increasing the level of exports and allocating government spending to productive things.